037 Apparent homozygous c.830G>A GNE myopathy in non-jewish Iraqi. Issue 9 (12th August 2022) - Sim, Nicholas Keyi; Ismail, Azzam; Busby, Mark; Cord, Spilker
Abstract : GNE myopathy is an adult-onset autosomal recessive distal myopathy uniquely characterised by quadri- ceps sparing. It was previously described in Japanese patients and a large ethnic cluster was identified in Jews originating from Iran. Since then, it is recognised to have a worldwide prevalence with multiple pathogenic variants. While compound heterozygous c.830G>A GNE myopathy has previously been reported, homozygous disease has only previously been reported in a non-Jewish Iranian cohort and the Indian subcontinent. Here we report a case of apparent homozygous c.830G>A GNE myopathy in a non-Jewish Iraqi patient.